Analysis of Energy Loss of Distribution Network of PT. PLN (Persero) ULP Banda Aceh - Haz, Fauzia; Anshar, Andi Ahmad Fauzan; Setia, Giri Angga; Winanti, Naftalin; Daelami, Ahmad (Jurnal Teknologi Elekterika, 2025)
The aim of this research to identify areas requiring further attention to enhance electricity distribution efficiency. Data collection is conducted through observation and documentation methods to obtain secondary data such as Single Line Diagram, Distribution Transformer Load Current, Substation Voltage, Conductor Type, Conductor Length, and Conductor Cross-Sectional Area. Secondary data is processed and analyzed to obtain the conductor resistance value, conductor/line power losses, transformer power losses, total power losses, and total energi losses occurring in the distribution network using mathematical calculations, followed by simulation using the ETAP (Electrical Transient Analysis Program) application. After manually calculating power losses in the PT. PLN (Persero) ULP Banda distribution network at Penyulang Nusantara, which reached 7.84034 kW, the simulation results using the ETAP software show 7.8 kW, with a power loss percentage of 0.69% relative to the load. Following the simulation of improvement efforts using ETAP (conductor uprating and load balancing), power losses decrease to 4.4 kW (a reduction of 3.4 kW), with a percentage of 0.39%. The energi losses before improvement are 5,645.045 kWh (1.802%), and after improvement, it becomes 3,168 kWh (a reduction of 2,477 kWh) with a percentage of 1.59%. The improvement efforts result in savings of IDR 3,578,586.91.